Pekerja Sosial Sekolah Sebagai Peran, Tantangan, dan Peluang dalam Konteks Pendidikan - Chriestine Lucia Mamuaya (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
School social workers have a strategic role in supporting the welfare of students in Indonesia, especially in dealing with various social, emotional, and psychological issues that can affect academic performance. As a liaison between students, families, schools, and the community, school social workers play a role in providing interventions that aim to create an inclusive, safe, and supportive learning environment. However, the implementation of this role still faces various challenges, such as the limited number of professionals, the lack of support for facilities in schools, and social stigma against the social worker profession. This condition hinders the optimization of student welfare services as a whole. This article aims to explore the role of school social workers in the context of Indonesian education, identify the challenges faced, and examine opportunities for role strengthening through holistic intervention approaches and policy support. The results of the study show that increasing the effectiveness of school social workers can be achieved through the integration of student welfare programs into the curriculum, ongoing training for social workers, and synergy between the government, schools, and local communities. Strong policy support and adequate resource allocation are decisive factors in strengthening the function of school social workers. With the right approach, school social workers have the potential to be agents of change in creating an education system that is more responsive to students' social and emotional needs, as well as encouraging the creation of a healthy and sustainable learning climate.